Method for detecting a tandem repeat - Georgiou,P; Yu,L-S; Malpartida-Cardenas,K; Fisher,M; Moser,N; Rodriguez,Manzano J (2019)
The present application relates to methods for detecting a tandem repeat in a nucleic acid sequence under isothermal conditions using primers.